2001
DOI: 10.1029/2001jb000431
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study into the rheology of synthetic polycrystalline coesite aggregates

Abstract: Abstract. Coesite has been found as a relic in ultrahigh pressure metamorphic (UHPM) crust worldwide and is expected to play a major role in the mechanical behavior of continental crust at UHPM conditions. We performed triaxial compression tests on synthetic polycrystalline coesitite in a solid medium apparatus at confining pressures of 3.1 to 3.7 GPa, temperatures of 700 ø to --1160øC, and strain rates betweeen 6x10 -7 and lx10 -3 s -•. The problem of the limited stress resolution of the solid medium apparatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 56 publications
(8 reference statements)
5
35
0
Order By: Relevance
“…Moreover, many HP and UHP metamorphic rocks have remained nearly undeformed (Biino and Compagnoni 1992;Liou and Zhang 1997;Renner et al 2001;Oberha¨nsli et al 2002;Sto¨ckhert 2002). This requires that deformation during subduction and exhumation be localized into weak shear zones.…”
Section: Rock Rheology: General Conceptsmentioning
confidence: 96%
“…Moreover, many HP and UHP metamorphic rocks have remained nearly undeformed (Biino and Compagnoni 1992;Liou and Zhang 1997;Renner et al 2001;Oberha¨nsli et al 2002;Sto¨ckhert 2002). This requires that deformation during subduction and exhumation be localized into weak shear zones.…”
Section: Rock Rheology: General Conceptsmentioning
confidence: 96%
“…For subduction channels, we used quartz-controlled rheology for P < 3.5 GPa and polycrystalline coesite rheology for P ≥ 3.5 GPa as in the previous study (Ichikawa et al 2013b). Namely, A = 6.7 × 10 −6 s −1 Mpa −n , n = 2.4, E * = 156 kJ/mol, and V * = 0 (Ranalli 1995, 1997) for P < 3.5 GPa and A = 10 −1.6 s −1 Mpa −n , n = 2.9, E * = 261 kJ/mol, and V * = 0 (Renner et al 2001) for P ≥ 3.5 GPa. For the mantle wedge, flow law parameters proposed by Kawazoe et al (2009) are used for dry and wet mantle rheologies.…”
Section: Rheological Parametersmentioning
confidence: 98%
“…Some authors have argued that rocks under geological conditions are too weak to support significant overpressure (e.g. Brace et al, 1970;Ernst, 1971;Burov et al, 2001;Renner et al, 2001;Green, 2005). Yet, Stüwe and Sandiford (1994) suggested that petrologically derived P-T paths may not record depth changes only but stress changes.…”
Section: Influence Of Tectonic Overpressure On the P-t Paths Of (U)hpmentioning
confidence: 99%